2005
DOI: 10.1080/00016470510030526
|View full text |Cite
|
Sign up to set email alerts
|

Migration of the acetabular component: Effect of cement pressurization and significance of early radiolucency

Abstract: Pressurization of the cement produced better cement penetration and increased the cup stability in terms of changes in inclination. Early findings of radiolucent lines can predict later unfavorable cup migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 40 publications
1
17
0
1
Order By: Relevance
“…With a power of 0.8 and a significance level of 0.05, at least 17 patients were needed in each group. These assumptions were confirmed by the results reported by Flivik et al [11]. Allowing for a loss to followup rate of 15%, an initial aim of 20 patients per group was set.…”
Section: Methodssupporting
confidence: 61%
“…With a power of 0.8 and a significance level of 0.05, at least 17 patients were needed in each group. These assumptions were confirmed by the results reported by Flivik et al [11]. Allowing for a loss to followup rate of 15%, an initial aim of 20 patients per group was set.…”
Section: Methodssupporting
confidence: 61%
“…Cementing techniques such as pressurisation were found useful in increasing the mechanical interlocking and stability of the interface (Oates et al, 1995;Flivik et al, 2005). Several methods have been used to evaluate interdigitation.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Flivik et al (2005) revealed the precision with a cemented cup, and the subsequent studies by Önsten et al (1994), Valstar et al (1997), andThanner et al (2000) reported the precision with an uncemented acetabular component. All studies were performed with the use of tantalum markers, with the exception of the study by Valstar et al (1997) who used the hemispherical cup algorithmbased RSA system.…”
Section: Discussionmentioning
confidence: 93%
“…This contrasts with the Monoblock cup used in the present study, which consists of the highly radiopaque tantalum metal. Flivik et al (2005) used an all-polyethylene cup, the Opticup, where all markers could be identified in a straightforward manner. When the hemispherical cup algorithm RSA software was applied to the hemispherical cup, the confidence interval of the translation along all axes was wider than with the conventional RSA system or the MbRSA system.…”
Section: Discussionmentioning
confidence: 99%